Young people's understandings of youth suicide: A qualitative study - LABOR, MELANIE NICOLE (Trinity College Dublin. School of Social Work & Social Policy. Discipline of Social Studies, 2020)
In Ireland, youth suicide is a serious public health issue accounting for approximately thirty percent of all deaths among young people aged between 15 and 24 years old. Youth suicide has received considerable attention from academics, policy makers and campaigners. Nonetheless, the phenomenon has commonly been approached from a singular medicalized perspective. By contrast, the youth perspective has received far less attention. Hence, this was a poorly understood topic. This study asked: what does youth suicide mean to young people in Ireland? The present study aims to gain a better understanding of the meanings of youth suicide, seeking to build a conceptual framework. This will be achieved by exploring participants' individual understandings of suicide in relation to local community discourses, norms, values and beliefs. This study makes an original contribution to suicidology by exploring the phenomenon from the youth perspective leading to greater conceptual clarity. This research offers an alternative reading of suicidality in addition to the dominant bio-psycho-medical model encouraging new approaches to suicide prevention. This study views suicide as a multifactorial phenomenon and that young people's constructions of suicide are subjective. This research is underpinned by a symbolic interactionist theoretical perspective which asserts that meanings are socially constructed through one's interactions with social phenomena. Hence, the meanings young people attribute to youth suicide are shaped by local norms, values and beliefs. This is a constructivist grounded theory study. Data were generated through qualitative interviews with 25 young men and women between 18 and 22 years old who lived in Dublin. Participants were selected based on the criteria that they were neither bereaved by suicide nor experienced suicidal ideation within the twelve months prior to the interview. Data was analysed simultaneously and iteratively. The study resulted in a conceptual framework through initial, focussed and theoretical coding consisting of five core categories: i) Perceptions of suicide, ii) Stigmatisation of suicidality, iii) Problems associated with suicide, iv)Explanations of suicide and v) Help-seeking behaviour: barriers and facilitators. These categories are underpinned – primarily – by concepts of stigma and shame, as well as traditional understandings of gender.
APPROVED
Keywords: Youth; Suicide; Meanings; Perceptions; Qualitative